Penataan Kembali Jaringan Distribusi Radial Menggunakan Modified Firefly Algorithm (MFA) Pada Penyulang Jogorogo Ngawi - Machrus Ali; Miftachul Ulum (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2017)
The configuration of radial distribution networks is very diverse and difficult to simplify. Reconfiguration of the distribution network is used to reset the network configuration form by opening and closing switches found on the distribution network. Reconfiguration of the distribution network is needed to reduce power losses and improve system reliability. The number of feeders and buses on the network requires a very long time if calculated manually. Because of that, it is necessary to solve problems using artificial intelligence or AI. Firefly Algorithms (FA) are widely used in research to solve optimization problems. Modified Firefly Algorithms (MFA) is an FA modification designed to solve optimization problems in a discrete combination. MFA can find the best network reconfiguration so that it can reduce losses and improve the voltage at the end point of this method can later use other artificial intelligence or can be applied to other feeders, so as to reduce electrical energy losses.